Лазерная диагностика потоков. Часть 2. Параметры элементов оптических схем ЛДИС - Никитин, А. М. (НТУ "ХПИ", 2005)
In this article estimations of the optical parameters schemes LDA adapted to measuring of stream performances of restricted transparency fluids are reduced. Efficiency of algorithm at a phase of layout LDA optical schemes is show
Keywords: лазерные доплеровские измерители скорости; лазерный пучок; бегущие интерференционные волны; мощность излучения